Depression: more treatment but no drop in prevalence. Issue 4 (July 2019) - Ormel, Johan; Kessler, Ronald C.; Schoevers, Robert
Abstract : Purpose of review: Since the 70s, treatment of depression, especially pharmacologically, has expanded enormously. However, epidemiological studies show that 12-month population prevalence rates have not dropped. This observation raises multiple questions. How good are treatments of depression actually? Do they improve long-term outcomes? Have the treatment gaps narrowed? And how can we make mental healthcare more effective at the population level? Recent findings: Recent publications suggest some answers. Controlled treatment trials show that effectiveness of specific treatments (pharmacological, psychological) is modest and probably overestimated owing to substantial spontaneous recovery and nonspecific therapeutic effects. Treatment gaps are still substantial and prevention has unclear long-term effects and is not structurally embedded. Future relevance of genetic information for better personalized treatment is potentially high but uncertain. Increasingly, the potential of treatment to improve long-term outcome is being questioned. Summary: To reduce prevalence, it is essential to narrow the treatment gaps, provide timely interventions and high-quality treatment, eradicate waiting lists, prescribe antidepressants more cautiously and better managed, consider psychological alternatives, and provide more psychosocial treatment in primary care with physician-assistants. In addition, research is needed on long-term outcome of different treatment modalities, and least but not last the value of structurally socially embedded preventive interventions.